Eesti elanike suhtumine kohustuslikku usundiõpetusse - Schihalejev, Olga (Usuteaduslik Ajakiri, 2025)
Estonian Residents' Perspectives on Compulsory Religious Education Religious education in the context of general education has been a controversial issue in Estonia for several decades. Although non-confessional religious education is included in national curricula for basic school and for upper secondary schools, the subject of religious education can be found as elective only in few schools, almost exclusively at upper secondary level. The article distinguishes between confessional and non-confessional religious education in Estonia. The main focus of the article is the attitudes to compulsory courses of non-confessional religious education based on the survey „On Life, Religion, Religious Life“ conducted in 2020. In doing so, attitudes according to respondents’ age, education, religious background and other questions are analysed. Strong support of churches may become obstacle to religiously sceptical people, especially if it is coupled with dis-support of educational authorities.